A preliminary field survey of ectoparasites of rodents in urban park, Sarawak, Malaysian Borneo - Madinah, A.; Mariana, A.; Fatimah, A.; M. T, Abdullah (Tropical Biomedicine, 2013)
A survey of ectoparasites was carried out during Eco-Zoonoses Expedition in Bukit Aup Jubilee Park (BAJP), Sibu, Sarawak, Malaysian Borneo from 5(th) to 9(th) June 2008. A total of nine individuals comprising two species of rodents were captured. The species of rodents screened for ectoparasites were Sundamys muelleri and Callosciurus notatus. Four genera and six species of ectoparasites were collected, namely, Ixodes granulatus, Ixodes sp., Laelaps sedlaceki, Laelaps nuttalli, Hoplopleura dissicula and Listrophoroides sp. Three species of the ectoparasites are known to have potential health risk. The species were Ixodes granulatus, Laelaps nuttalli and Hoplopleura dissicula. This survey produced the first list of ectoparasites in Bukit Aup Jubilee Park, Sarawak, Malaysia.